Pengaruh Terapi Musik Bahasa Inggris terhadap Tingkat Stres pada Lansia di Desa bangun Rejo Kecamatan Tanjung Morawa Tahun 2024 - Zulkarnain Batubara; Rosmega Rosmega; Aldo Palijama; Yester Lastiur Simamora; Ali Imran (Jurnal Riset Ilmu Kesehatan Umum dan Farmasi (JRIKUF), 2024)
Background: Stress occurs in the elderly due to unpleasant pressure or disturbances that are usually created when the elderly see a mismatch between the circumstances and the natural resource systems they have. One technique that can be used to reduce stress in the elderly is classical music therapy. The purpose of this study was to determine the effect of English music therapy on stress levels in the elderly in Bangun Rejo Village, Tanjung Morawa District in 2024. Method: This study is a type of quantitative research with a Pretest and Posttest with Control Group design. Data collection was carried out using a questionnaire. The number of respondents was 28 people with a simple random sampling technique. The data obtained were processed statistically using the Marginal Homogeneity formula. Results: Based on the results of the analysis, it was obtained that out of 30 respondents, most had age characteristics of 70-74 years as much as 56.7% and 45-47 years as much as 5.1%. The majority of respondents had moderate stress levels as much as 14 (46.7%) before therapy, after therapy the stress level decreased by 16 (53.3%) in the normal stress category. Conclusion: There is an effect of classical music therapy on stress levels in the elderly with a p value = 0.000.